The Issue of Interrelationship between Plot and Fabula - JRBASHYAN, ASHKHEN (Bulletin of Yerevan University B: Philology, 2021)
The tradition of differentiating the plot and the fabula has originated from the works by Russian formalists and states the relationship between life material and its elaboration in narrative texts. This very dichotomy gave incentives for the development of narratology as a science. In modern literary theory the usage of such oppositions, as narration and discourse, plot scheme and plot are more widely used. The difference between the plot and fabula must not be reduced to the expression of time succession solely in literary works. The plot is the result of complex transformations of the “raw” material. It involves the narrator’s viewpoint, ideological assessment, emphasizing of the dominant theme and also the means of temporal expression of the events.